Use of evidence-based study techniques in medical students, Peru. - Atencio Paulino, Joel Isaac; Galarza Caceres, Deivi Nick; Santivañez Lazo, Angely Adriana; Huaman Julian , Lecsi Katerin; Huaripata Safora , Michelle Milena; Condor Elizarbe, Ivan Roli (Medicina Clínica y Social, 2023)
Introduction: The use of evidence-based techniques by students is a fundamental method for learning. Objective: To evaluate the frequency of the use of evidence-based study techniques in medical students from a university in Peru. Methods: A cross-sectional observational study was carried out with 75 students of human medicine from the National University of Central Peru through a survey that collected study techniques and other variables, selected by non-probabilistic sampling. Results: (58.73%) were male, one (58.7%), did not use evidence-based study techniques, low-medium family socioeconomic level (33.3%). The most used study material was books (58.14%), followed by scientific articles (24%); (45.3%) spent between 4-6 hours studying and (40%) used the "Active recall" technique. For their part, (53.3%) enjoyed studying "sometimes", (70.7%) postponed studying "sometimes" and (62.7%) had difficulty concentrating "sometimes". Furthermore, our findings indicate that those who studied for less than 2 hours preferred educational videos, while students who dedicated 6-8 hours chose to engage with reading books, scientific articles, and evidence-based slides. Similarly, those encountering difficulties 'most of the time' tended to overuse slides, whereas those facing difficulties 'always' favored educational videos (p
Keywords: utilization of techniques; learning; evidence-based medicine; medical students